2017
DOI: 10.3389/fonc.2017.00294
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Merkel Cell Polyomavirus DNA in Serum Samples of Healthy Blood Donors

Abstract: Merkel cell polyomavirus (MCPyV) has been detected in 80% of Merkel cell carcinomas (MCC). In the host, the MCPyV reservoir remains elusive. MCPyV DNA sequences were revealed in blood donor buffy coats. In this study, MCPyV DNA sequences were investigated in the sera (n = 190) of healthy blood donors. Two MCPyV DNA sequences, coding for the viral oncoprotein large T antigen (LT), were investigated using polymerase chain reaction (PCR) methods and DNA sequencing. Circulating MCPyV sequences were detected in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…MC polyomavirus was detected in 3.8% of serum samples in our study, which is comparable to findings in other studies. For example, a study of 190 blood donors reported MCPyV in 2.6% of sera and another study of 621 sera from 394 elderly hospitalized patients older than 65 years of age found a prevalence of 9.9% for MCPyV, which suggests that the prevalence may increase with age. MCPyV has been detected in other blood compartments, for example, in 22% of buffy coats from blood donors .…”
Section: Discussionmentioning
confidence: 99%
“…MC polyomavirus was detected in 3.8% of serum samples in our study, which is comparable to findings in other studies. For example, a study of 190 blood donors reported MCPyV in 2.6% of sera and another study of 621 sera from 394 elderly hospitalized patients older than 65 years of age found a prevalence of 9.9% for MCPyV, which suggests that the prevalence may increase with age. MCPyV has been detected in other blood compartments, for example, in 22% of buffy coats from blood donors .…”
Section: Discussionmentioning
confidence: 99%
“…RNA was quantified by using a Nanodrop spectrophotometer (ND‐1000; NanoDrop Technologies, Wilmington, Delaware) . The Human Osteogenesis RT 2 Profiler PCR Array (Qiagen) was used as described . Specific primers sets used in real‐time PCRs were used to analyze the expression of 84 genes involved in different pathways, such as osteogenic differentiation, cartilage condensation, ossification, bone metabolism, bone mineralization, binding to Ca 2+ and homeostasis, extracellular matrix (ECM) protease inhibitors, adhesion molecules, cell‐to‐cell adhesion, adhesion molecules of the ECM, and growth factors.…”
Section: Methodsmentioning
confidence: 99%
“…17,21 The Human Osteogenesis RT 2 Profiler PCR Array (Qiagen) was used as described. 17,22 Specific primers sets used in real-time PCRs were used to analyze the expression of 84 genes involved in different pathways, such as osteogenic differentiation, cartilage condensation, ossification, bone metabolism, bone mineralization, binding to Ca 2+ and homeostasis, extracellular matrix (ECM) protease inhibitors, adhesion molecules, cell-to-cell adhesion, adhesion molecules of the ECM, and growth factors. For data analysis, the fold change (FC) of each gene expression was calculated by using the 2 −ΔΔCt method, whereas housekeeping genes, used as controls, were used to normalize results and Log 2 FC; <1 or >1 was considered significant.…”
Section: Osteogenesis Rt 2 Profiler Pcr Arraymentioning
confidence: 99%
“…Serologic studies indicate that exposure to MCPyV is widespread (DeCaprio, 2017;van der Meijden et al, 2011). Viral DNA is present in 2.6% of healthy blood donors (Mazzoni et al, 2017). Primary exposure to MCPyV begins in childhood after a period of immunity from maternal antibodies (Martel-Jantin et al, 2013;Nicol et al, 2013).…”
Section: Merkel Cell Polyomavirusmentioning
confidence: 99%